An Aristotelian interpretation of the New Spain - Zagal, Héctor (Tópicos, Revista de Filosofía, 2013)
Just as Aristotle sets dialectically a series of deep aporias or apparently irresoluble problems in Metaphysics II, Virginia Aspe does something similar in Las Aporías Fundamentales del Periodo Novohispano in order to understand the philosophy of the three centuries of the Viceroyalty. From among the oppositions that constitute the aporia of the Mexican philosophical thought collected in Aspe’s work, the following binomials stand out: civilization-barbarism, nature-liberty, nature-culture, providentialism-liberty and reason-faith. Besides making a brief revision of Aspe’s work, the author offers an even briefer reflection on the Conquest, the Viceroyalty, the Baroque and the Mexican mentality.